PREVALENCE OF THE FEMALE ATHLETE TRIAD AMONG JUNIOR FEMALE LONG DISTANCE RUNNERS IN ITEN, ELGEYO-MARAKWET COUNTY, KENYA - MUIA, ESTHER NDUKU (My University, 2015)
Adolescents regularly participating in sports and do not meet their energy intake may develop several medical conditions, such as disordered eating, menstrual dysfunction, and decreased bone mineral density, collectively referred to as the Female Athlete Triad (FAT). Limited data is available on components of FAT in adolescent athletes of African descent. This study’s aim was to investigate the presence of the components of the female athlete triad amongst a group of junior long female distance runners and non-athletes in Kenya. One hundred and ten students randomly selected from secondary schools in Iten, Elgeyo-Marakwet County, took part in this cross-sectional comparative study. Students completed demographic, health, sport and menstrual history questionnaires as well as a 5-day weighed dietary record and exercise log to calculate energy availability (EA). Heel bone mineral density was assessed with ultrasound. Subscales of the Eating Disorder Inventory and the cognitive dietary restraint subscale of the Three-Factor Eating Questionnaire measured disordered eating. Dietary intake was analysed with Nutrisurvey and dietary diversity determined by the Individual Dietary Diversity Score (IDDS) using 5-day dietary records. Fewer mothers (19 vs. 40%, χ2=12.9, p=0.02) and fathers (28 vs. 50%, χ2=11.8, p=0.06) from athletes had tertiary education than non-athletes, and more mothers from non-athletes had formal employment than athletes (54 vs.13%, χ2=22, p<0.001). Energy availability was significantly lower in athletes than non-athletes (36.5 ± 4.5 vs. 39.5 ± 5.7 kcal/kg/FFM/day, p=0.003). More athletes than non-athletes were identified with clinical low EA (17.9 vs. 2 %, [OR = 9.5, 95% CI (1.17, 77), p=0.021). Subclinical (75.4 vs. 71.4%) and clinical DE behaviour was similar between athletes and non-athletes, (4.9 vs. 10.2%, respectively, χ 2=1.1, p=0.56). More athletes than non-athletes had a body mass index of < 17.5 kg/m2 [16.1 vs. 0%, OR= 0.8, 95% CI (0.7, 0.9), p=0.004]. No significant differences were noted for carbohydrate, fat, calcium, magnesium, B2 and zinc intake between groups. IDDS was higher in students in day schools than in boarding schools (4.36±0.7 vs. 3.8±0.6, χ2 =13.4, p=0.001). More athletes (72.1% vs. 32.7% χ 2 =17, p=0.000) reported restricting the types of food eaten and the amount to control weight (68.9% vs. 32.7%, χ2 =14, p=0.000). More athletes reported clinical menstrual dysfunction in comparison to non-athletes (32.7% vs. 18.3%, χ 2=7.1 p=0.02); primary amenorrhea (13.1% vs. 2.0%) and secondary amenorrhea (19.7% vs. 10.2%). BMD tended to be higher in athletes compared to non-athletes (0.629±0.1 vs. 0.592±0.1 g/cm2 , p=0.06). Kenyan adolescent athletes and non athletes present with low energy availability and menstrual disturbances which are key components of the female athlete triad. Energy intakes should be increased in the student population to match the energy expended and menstrual disturbances closely monitored in athletic adolescent girls since exercise induced amenorrhea signals energy drain.